2014
DOI: 10.1002/ar.22865
|View full text |Cite
|
Sign up to set email alerts
|

Computed Tomography and Gross Anatomical Studies on the Head of One‐Humped Camel (Camelus dromedarius)

Abstract: The current study aimed to document by computed tomography (CT) the anatomical structures of the one-Humped camel head relative to their adaptability to living environments. Seven adult one-Humped camels' heads were used in this study. The structures of the nasal cavity, paranasal sinuses, oral cavity, orbit, and cranium were investigated using computed tomographic scans, cross, and sagittal sections of the head cadavers, and skulls. The study showed the nasal conchae had special properties where the dorsal na… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
64
3
2

Year Published

2015
2015
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(75 citation statements)
references
References 22 publications
6
64
3
2
Order By: Relevance
“…Concerning the paranasal sinuses, the present investigation revealed four sinuses: maxillary, frontal, lacrimal and sphenoidal, in matching the findings of Acar et al, (), Mladina () and Skitarelić and Mladina () in lamb. The palatine sinus was added in; sheep (May, ; Sisson, ), goat (Kareem & Sawad, ), buffalo (Alsafy et al, ; Moustafa & Kamel, ; Saigal & Khatra, ) and camel (Alsafy et al, ), while the sphenoidal sinus was inconstant in buffalo (Alsafy et al, ; Moustafa & Kamel, ; Saigal & Khatra, ) and could not be observed in goat (Kareem & Sawad, ). Moreover, the nasal sinuses in our study showed the dorsal conchal, middle conchal and ethmoidal sinuses with unnoticeable ventral nasal conchal sinus, that came in line with the results of May () and Sisson () in sheep, Moustafa and Kamel (), Saigal and Khatra () and Alsafy et al () in buffalo and Alsafy et al () in camel.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Concerning the paranasal sinuses, the present investigation revealed four sinuses: maxillary, frontal, lacrimal and sphenoidal, in matching the findings of Acar et al, (), Mladina () and Skitarelić and Mladina () in lamb. The palatine sinus was added in; sheep (May, ; Sisson, ), goat (Kareem & Sawad, ), buffalo (Alsafy et al, ; Moustafa & Kamel, ; Saigal & Khatra, ) and camel (Alsafy et al, ), while the sphenoidal sinus was inconstant in buffalo (Alsafy et al, ; Moustafa & Kamel, ; Saigal & Khatra, ) and could not be observed in goat (Kareem & Sawad, ). Moreover, the nasal sinuses in our study showed the dorsal conchal, middle conchal and ethmoidal sinuses with unnoticeable ventral nasal conchal sinus, that came in line with the results of May () and Sisson () in sheep, Moustafa and Kamel (), Saigal and Khatra () and Alsafy et al () in buffalo and Alsafy et al () in camel.…”
Section: Discussionmentioning
confidence: 99%
“…Paranasal sinuses were excavations in some skull bones, and their wall is composed of compact bone lined by respiratory epithelium which directly or indirectly continues with the nasal cavity (Dyce, Sack, & Wensing, ; König & Liebich, ; Sisson, ). The morphology of these sinuses is studied in several animals: small ruminants (May, ; Sisson, ), domestic animals (Dyce et al, ; Frandson, Wilke, & Fails, ; König & Liebich, ), buffalo (Alsafy, El‐Gendy, & El Sharaby, ; Farag, Hagrass, Daghash, El‐Bably, & Sary, ; Moustafa & Kamel, ; Saigal & Khatra, ) and camel (Alsafy, El‐Gendy, & Abumandour, ). As the relevant clinical applications in correlation to the gross anatomy of the paranasal sinuses are remained inadequate especially in sheep, so, it is necessary to understand the definite position, extension and communication of these sinuses for improvement the diagnosis of the upper respiratory tract disorders (Losonosky, Abbott, & Kuriashkin, ; Reetz, Mai, Muravnick, Goldschmidt, & Schwarz, ).…”
Section: Introductionmentioning
confidence: 99%
“…A descrição das cartilagens nasais se apresenta conforme o relatado por esses autores para as demais espécies. Da mesma forma, a morfologia da cavidade nasal com suas conchas e meatos foi observada de acordo com a descrição desses autores e também como visto mais especificamente em camelos por Alsafy et al (2014). Nos animais utilizados neste estudo, apenas as características macroscópicas das conchas e meatos nasais puderam ser analisadas.…”
Section: Discussionunclassified
“…Preservations of flexible models of hollow organs and many dried anatomical specimens were prepared (Arnautovic et al, 2005;McKiernan & Kneller, 1983;Updike & Holladay, 1986). Many studies to learning sectional anatomy by computed tomography (CT), magnetic resonance imaging (MRI), contrast radiography, ultrasonography and cadaver sectional anatomy (Alsafy et al, 2013(Alsafy et al, , 2014Alsafy, 2008;Desbrosse et al, 2008;Garland et al, 2002;Morgan et al, 2006;Puchalski, 2012 Table I. Percentages of student's perception of the educational design and content (Q1-Q10) as well as overall perception of Equine Anatopedia (Q11-Q20).…”
Section: Discussionmentioning
confidence: 99%